Effects of Ginkgo Diterpene Lactone Glucosamine Combined with Clopidogrel on Hemodynamics and Neurocytokines in Patients with Cerebral Infarction Complicated by Coronary Heart Disease - Zhu, Shengjiao; Chen, Guoqiang (Journal of Medical Biochemistry, 2025)
Background: This study investigates the effects of Ginkgo Diterpene Lactone Meglumine (GM) combined with Clopidogrel (CLO) on hemodynamics, neurocytokines, and inflammatory responses in patients with cerebral infarction (CI) complicated by coronary heart disease (CHD). Methods: A total of 152 patients diagnosed with CI complicated by CHD, admitted to our hospital between January 2024 and October 2024, were enrolled in the study. Among them, 81 patients received CLO monotherapy (control group), while the remaining 71 patients were treated with a combination of CLO and GM (observation group). Hemodynamic parameters, including plasma viscosity (PV), whole blood high (WBHSV) and low shear viscosity (WBLSV), as well as reduced viscosity (RV), were measured before and after treatment. Platelet adhesion test (PAdT) and platelet aggregation test (PAgT) were also performed. Inflammatory markers and neurocytokines were assessed using ELISA, and adverse reactions during treatment were documented. Results: After treatment, both groups exhibited significant reductions in PAdT, PAgT, PV, HBV, LBV, and RV compared to baseline (P<0.05). However, the observation group demonstrated greater reductions in PAdT, PAgT, LBV, and RV than the control group (P<0.05). Additionally, the observation group showed lower levels of NSE, GFAP, TNF-α, and hs-CRP, along with higher levels of BDNF, compared to the control group (P<0.05). No significant difference was observed in the incidence of adverse reactions between the two groups (P>0.05). Conclusion: The combination of GM and CLO is more effective than CLO monotherapy in improving hemodynamics, enhancing neurological function, and mitigating inflammatory responses in patients with CI complicated by CHD.